T-Stable-extending Modules and Strongly T- stable Extending Modules - Hadi, Inaam Mohammed Ali; Shyaa, Farhan Dakhil (Iraqi Journal of Science, 2020)
In this paper we introduce the notions of t-stable extending and strongly t-stable extending modules. We investigate properties and characterizations of each of these concepts. It is shown that a direct sum of t-stable extending modules is t-stable extending while with certain conditions a direct sum of strongly t-stable extending is strongly t-stable extending. Also, it is proved that under certain condition, a stable submodule of t-stable extending (strongly t-stable extending) inherits the property.